Perspectives of Health Care Providers Working with HIV Positive Clients on Nutritional Challenges Among People Living with HIV/AIDS in Kigali, Rwanda - Tafadzwa Dzinamarira; Gashema Pierre; Michael Habtu; Rosemary Okova (Journal of Public Health International, 2020)
Efforts to control the Human Immunodeficiency Virus epidemic in Rwanda have seen remarkable success over the years. Effective antiretroviral therapy has played great role in improving longevity among people living with HIV/AIDS (PLWH). While this is the case, there are various nutritional challenges, which are often faced, among PLWH. Guided by the Rwanda country guidelines for nutritional management for PLWH and WHO recommendations, this study aimed to explore the perspectives of health care providers (HCPs) working with PLWH on nutritional challenges faced by their clients in Kigali, Rwanda. We conducted a qualitative study using in-depth interviews to collect data. A non-probability purposive sampling was employed to recruit HCPs. Data analysis was based on the naturalistic paradigm. We followed the hybrid approach in conducting thematic analysis. Three themes were identified. First, HCPs had good knowledge on nutritional requirements for PLWH. They demonstrated good communication skills and adequate counseling skills that were necessary for addressing concerns on nutrition from their clients. Secondly, it emerged that HCPs perceived a lack of resources to be the major challenge faced in nutritional management of their clients. From theme three, it emerged that, from HCPs experiences, food insecurity and lack of feeding supplements were the main causes of malnutrition among PLWH in Kigali, Rwanda. From the HCPs perspective, there is a need to improve healthcare institutions capacity to manage nutritional challenges faced by PLWH. To achieve this, policy makers need to channel adequate resources for this cause.
Keywords: Health care provider